Short-term outcomes of downreferral in provision of paediatric antiretroviral therapy at Red Cross War Memorial Childrens Hospital, Cape Town - Copelyn, Julie (Department of Paediatrics and Child Health, 2017)
Background: The large scale-up of paediatric HIV care necessitated down-referral of many children receiving antiretroviral therapy (ART) from Red Cross War Memorial Children's Hospital (RCWMCH). No published data exists on the outcomes of these children. Objectives: To assess clinical, immunological and virological outcomes of children receiving ART in the first 12 months after down-referral to primary health care (PHC) clinics, and identify determinants of successful down-referral. Methods: We conducted a retrospective cohort study of children <15 years of age who commenced ART at RCWMCH and were subsequently down-referred to one of two PHC clinics between January 2006 and December 2012. Baseline characteristics of patients and caregivers as well as CD4 counts, viral loads and weights were collected at 6 and 12 months post-down-referral. Outcomes included retention in care and viral suppression. Results: One hundred and sixteen children down-referred to Heideveld and Gugulethu were included. After down-referral 13.8% of the cohort never arrived at the designated clinic and 10% took longer than 8 weeks, therefore probably experiencing treatment interruption. At 12 months post down-referral only 68.2% remained in care at the designated clinics. No factors were associated with retention in care. For those children who remained in care at the PHC clinics, the clinical and immunological gains achieved prior to down-referral were sustained through 12 months of follow up, and 54.7% of the retained cohort had documented viral suppression at 12 months. Conclusion: Down-referral of children on ART is a vulnerable process with risk of loss to follow-up and treatment interruption.